Did Personal Attitude Have a Role In the Entrepreneurship Circle? - Siti Nur Hasanah; Tsabita Khwarazmita (Universitas Muhammadiyah Malang, 2023)
The topic of student entrepreneurship is constantly interesting to discuss because it increases their motivation to foster entrepreneurial intentions within them. Meanwhile, the growth of entrepreneurship is indeed caused by several external and internal factors. Hence, this study aims to examine the effect of personal attitude support and mediation on entrepreneurial intentions, with a focus on management and business students. In its analysis and testing, this study adopts SEM-PLS utilizing Smart-PLS 4.0 as a complete to highlight analytical skills in one analysis program and increase the broad understanding of all research variables. The findings found in this study are the influence of support through personal attitudes positively and significantly affects entrepreneurship intention. The results of this study indicate that personal attitudes do not dominate as mediators, even though the results are good. However, personal attitudes can independently influence entrepreneurial intentions. Therefore, this study suggests several things that can further foster students' entrepreneurial intentions.